Review of Mexican Experience with the Regulation of Large Commercial Motor Vehicles - Transportation Research Board (The National Academies Press, 2011)
TRB's National Cooperative Highway Research Program (NCHRP) Research Results Digest 362: Review of Mexican Experience with the Regulation of Large Commercial Motor Vehicles reviews and summarizes the Mexican experience with changes in truck size and weight limits. The report also evaluates the potential applicability to size and weight limits in the United States.

Review of Mexican Experience with the Regulation of Large Commercial Motor Vehicles - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2011)
TRB2019s National Cooperative Highway Research Program (NCHRP) Research Results Digest 362: Review of Mexican Experience with the Regulation of Large Commercial Motor Vehicles reviews and summarizes the Mexican experience with changes in truck size and weight limits. The report also evaluates the potential applicability to size and weight limits in the United States.

Review of Canadian Experience with the Regulation of Large Commercial Motor Vehicles - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2010)
TRB2019s National Cooperative Highway Research Program (NCHRP) Report 671: Review of Canadian Experience with the Regulation of Large Commercial Motor Vehicles examines the process used in Canada to harmonize heavy truck size and weight regulations across the country. The report provides insights on how lessons learned from the Canadian experience might be applied in the United States.

TRB Special Report 303: Equity of Evolving Transportation Finance Mechanisms - Transportation Research Board (The National Academies Press, 2011)
TRB Special Report 303: Equity of Evolving Transportation Finance Mechanisms addresses the equity of alternatives to current transportation finance mechanisms, notably mechanisms based on tolling and road use metering (i.e., road pricing). The committee that developed the report concluded that broad generalizations about the fairness of high-occupancy toll lanes, cordon tolls, and other evolving mechanisms oversimplify the reality and are misleading. The fairness of a given type of finance mechanism depends on how it is structured, what transportation alternatives are offered to users, and which aspects of equity are deemed most important. The committee identified the various dimensions of equity important for public policy debates about evolving finance mechanisms, proposed specific issues for policy makers to consider when evolving mechanisms are proposed, and identified areas where future research is needed for a better understanding of the equity implications of such mechanisms. To move beyond superficial analysis, the report calls on policy makers to insist on well-designed studies of transportation finance that yield reliable information about the likely distribution of burdens and benefits, and that facilitate comparison of a given finance strategy with alternatives. In addition, public policy makers who wish to promote equity should engage their constituents and other stakeholders early and often when considering the use of new or unfamiliar transportation finance mechanisms. The report calls on researchers to explore further how people modify their use of the transportation system in response to changes in prices and services and the consequences of these responses. It also recommends the development of a handbook for state and local governments describing procedures for conducting equity analyses of transportation finance policies.

An Assessment of the National Highway Traffic Safety Administration's Rating System for Rollover Resistance: Special Report 265 - Transportation Research Board (The National Academies Press, 2002)
TRB Special Report 265 - An Assessment of the National Highway Traffic Safety Administration's Rating System for Rollover Resistance finds that the static stability factor is a useful indicator of a vehicle's propensity to roll over, but that U.S. government ratings for new cars, light trucks, and sport utility vehicles do not adequately reflect differences in rollover resistance shown by available crash data. According to the report, the five-star system should be revised to allow better discrimination among vehicles and incorporate results from road tests that measure vehicle control and handling characteristics. Following the National Highway Traffic Safety Administration's (NHTSA's) issuance of vehicle ratings to inform consumers about rollover risk, Congress requested a TRB study to evaluate the appropriateness of the rating system. Motor vehicle rollovers involving passenger cars, vans, pickup trucks, and sport utility vehicles result in approximately 10,000 deaths and 27,000 serious injuries each year in the United States. NHTSA developed a five-star rating system to inform consumers about the rollover resistance of passenger cars and light-duty passenger vehicle trucks. After thoroughly evaluating NHTSA's development of the rating system, the committee that conducted this study concurred with the agency's reliance on a static measure of vehicle stability but pointed out some inadequacies of the statistical model used to relate this static measure to rollover risk. Alternative statistical approaches would provide a better approximation of risk. The rating system itself was found wanting. The procedures used to develop and test the ratings with consumers through focus groups did not provide credible evidence that consumers understood the message about the actual risk associated with a given vehicle. By being limited to only five levels, the system also discarded valuable information. The data developed by NHTSA could be refined to enable consumers to discriminate better among vehicle models with regard to their rollover experience.

In Our Own Backyard: Principles for Effective Improvement of the Nation's Infrastructure - National Research Council
This volume takes a fresh look2014primarily from a technological perspective2014at the nation's \

Toward Infrastructure Improvement: An Agenda for Research - National Research Council (The National Academies Press, 1994)
This book advises the federal government on a national infrastructure research agenda. It takes the position that the traditional disciplinary and institutional divisions among infrastructure modes and professions are largely historical artifacts that impose barriers to the development of new technology and encourages the government to embrace a more interdisciplinary approach. In order to be practical, the study focuses on infrastructure technologies that can be incorporated into or overlay current systems, allow for alternative future alternative future urban development, and are likely to have value cutting across the distinct functional modes of infrastructure. Finally, the report is organized according to seven broad cross-cutting areas that should promote interdisciplinary approaches to infrastructure problems: systems life-cycle management, analysis and decision tools, information management, condition assessment and monitoring technology, the science of materials performance and deterioration, construction equipment and procedures, and technology management.

Experiences of Federal Agencies With Solar Energy Systems: Synopsis of a Workshop (The National Academies Press, 1985)

The Experiences of Federal Agencies with the Use of Competitive Negotiations for Procuring Construction (The National Academies Press, 1990)

The Experiences of Federal Agencies With Operations and Maintenance Contracts for Facilities (The National Academies Press, 1988)

Personal Cars and China - National Research Council; National Academy of Engineering (The National Academies Press, 2003)
This collaborative study between the NRC and the Chinese Academy of Engineering (CAE) addresses the problems facing China in the next twenty years as it attempts to provide personal transport desired by millions of Chinese, while preserving the environment and the livability of its cities. According to Song Jian, president of the CAE, the decision has already been taken to produce a moderate cost family car in China, which will greatly increase the number of vehicles on the roads. This study explores the issues confronting the country, including health issues, the challenge to urban areas, particularly the growing number of megacities, environmental protection, infrastructure requirements, and technological options for Chinese vehicles. It draws on the experience of the United States and other countries and review model approaches to urban transportation and land use planning. Recommendations and policy choices for China are described in detail.

Assessing the Research and Development Plan for the Next Generation Air Transportation System: Summary of a Workshop - National Research Council (The National Academies Press, 2008)
The U.S. aviation industry, airline passengers, aircraft pilots, airports, and airline companies are all facing challenges. The air transportation system is experiencing unprecedented and increasing levels of use. The federal government understands the critical need to update the U.S. air transportation system, and plans to implement the Next Generation Air Transportation System (NextGen) by 2025. This system is an example of active networking technology that updates itself with real-time shared information and tailors itself to the individual needs of all U.S. aircraft, stressing adaptability by enabling aircraft to immediately adjust to ever-changing factors. On April 1-2, 2008, a workshop was held at the National Academies to gather reactions to the research and development aspects of the Joint Planning and Development Office2019s baseline Integrated Work Plan (IWP), which is designed to increase the efficiency of airport and air space use in the United States. This book provides a summary of the workshop, which included presentations on the following topics: Airport operations and support; Environmental management; Air navigation operations, Air navigation support, and flight operation support; Positioning, navigation, and timing services and surveillance; Weather information services; Safety management; Net-centric infrastructure services and operations; and Layered adaptive security.

Use of Underground Facilities to Protect Critical Infrastructures: Summary of a Workshop - National Research Council (The National Academies Press, 1998)

Return on Investment in Transportation Asset Management Systems and Practices - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine
TRB's National Cooperative Highway Research Program (NCHRP) Research Report 866: Return on Investment in Transportation Asset Management Systems and Practices explores how transportation agencies manage their transportation assets, and provides guidance for evaluating the return on investment for adopting or expanding transportation asset management systems in an agency.As the term is most generally used, transportation asset management (TAM) entails the activities a transportation agency undertakes to develop and maintain the system of facilities and equipment2014physical assets such as pavements, bridges, signs, signals, and the like2014for which it is responsible. Based on the research team2019s work and the experiences of these agencies and others, the researchers describe a methodology that an agency may use to assess their own experience and to plan their investments in TAM system development or acquisition.A spreadsheet accompanies the research report helps agencies evaluate the return-on-investment of TAM systems.The tool allows users to summarize data from various simulation tools. The calculator also includes factors and procedures from the Highway Economic Requirements System State Version (HERS-ST) to estimate user benefits for pavement projects. It does not estimate user benefits for bridge projects.This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences, Engineering, and Medicine or the Transportation Research Board (collectively \

New Joint Sealants: Criteria, Design, and Materials: Publication No. 1006 (The National Academies Press, 1963)

Procedures Used to Assess the Condition of Federal Facilities (The National Academies Press, 1991)

New Techniques for Operating and Maintaining Federal Facilities: Proceedings of a Symposium (The National Academies Press, 1985)

Outer Continental Shelf Resource Development Safety: A Review of Technology and Regulation for the Systematic Minimization of Environmental Intrusion From Petroleum Products (The National Academies Press, 1972)

Impact Acceleration Stress: A Symposium - National Research Council (The National Academies Press, 1962)

Net Shape Technology in Aerospace Structures (The National Academies Press, 1986)